Time after time - Stone, Tamara Ireland (Hyperion, 2013)
Told from his point of view, continues the love story of Bennett, a time traveler from 2012 San Francisco, and Anna, sixteen, of 1995 Evanston, Illinois, as they try to make their relationship work despite his fear that it is not meant to be.